Mulheres negras e resistência: uma análise antropológica de narrativas sobre o acesso à educação superior em Redenção-CE - Braga, Ana Paula Fonseca (2021)
This research analyses female trajectories of young black women who had access to higher education, to discuss their perceptions about the intersections between gender and race relations. The study was carried out at Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB), conducted with young black women, students in Redenção and activists, enrolled in undergraduate courses at UNILAB. The proposal aims to produce anthropological knowledge about the social construction of the places female and their struggles for the right to appear and exist, providing opportunities for places of speech and the construction of more egalitarian gender relations. The supported hypothesis is that the policy of access to higher education is a marker in these trajectories, providing opportunities for personal reflections on forms of exclusion, oppression, prejudice and discrimination experienced. The research involves participant observation and the collection of semistructured interviews that explore the dimensions of family history, gender relations, religion, race relations, activism, access to education, etc. In this way, doing ethnography in this context means to provoke an uprooting, where we intend to unveil through dialogue, places of speech.